A4.5 Do High Molecular Weight Adiponectin Levels Associate with Radiographic Progression in early Rheumatoid Arthritis and Hand Osteoarthritis?. (25th February 2013) - Klein-Wieringa, IR; Andersen, SN; Kwekkeboom, JC; Herb-v.Toorn, L; Helm-van Mil, AHM van der; Meulenbelt, I; Huizinga, TWJ; Kloppenburg, M; Toes, REM; Ioan-Facsinay, A
Abstract : Background: Adipose tissue can secrete many different soluble factors (adipokines) influencing whole body metabolism. Some of these adipokines, such as adiponectin, have been shown to influence radiographic progression in osteoarthritis (OA) and rheumatoid arthritis (RA). In RA patients, total adiponectin (totAPN) levels in serum associate positively with radiographic progression, which suggestes an adverse effect on disease. Intruiguingly, in patients with hand OA, high totAPN levels in serum associated with a decreased relative risk for radiographic progression, suggesting a benificial effect on disease. Adiponectin is a pleiotropic adipokine, which consists of several isoforms. Of these isoforms, high molecular weight adiponectin (hmwAPN) has been described as one of the most biologically active and its effect on radiographic progression in RA and hand OA is unknown. Objective: Therefore, we explored the possibility that the association between totAPN and disease progression is primarily mediated by the hmwAPN isoform. Methods: Concentrations of hmwAPN and totAPN were determined in baseline plasma of 324 RA patients from the Early Arthritis Cohort (EAC) and in baseline sera of 164 hand OA patients from the Genetics Arthrosis and Progression (GARP) study. The association between levels of hmwAPN and totAPN with radiographic progression were determined using a multivariate normal regression model (EAC cohort) or by generalised estimated equations (GARP cohort). Adjustments were made for age, gender, treatment strategy and Body Mass Index (BMI). Results: In RA patients totAPN associated positively with radiographic progression (Sharp van der Heijde scores) (association estimate 3.65, p = 0.002), whereas in patients with hand OA, totAPN associated negatively with radiographic progression (joint space narrowing (JSN)) (Odds 0.24/Odds 0.21, p = 0.002/p = 0.002 two highest tertiles compared to the lowest tertile). HmwAPN on the other hand, did not associate significantly with radiographic progression in patients with hand OA or RA, although in patients with RA we did observe a trend towards a positive association (association estimate 1.53 p = 0.07) upon correcting for age, gender and treatment strategy. This trend was lost after further adjustment for BMI. Similar results were obtained when joint space narrowing (JSN) was used as outcome measurement. Conclusions: Our data further substantiate the connexion between APN-levels and radiographic progression in rheumatic disease and indicate that the differential effects associated between totAPN and radiographic progression in either in RA and hand OA is not mediated by (a selective effect of) hmwAPN.